2018
DOI: 10.1155/2018/1010248
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and FTY720 Alleviate Atherosclerosis by Cross Talk of Macrophage Polarization and Autophagy

Abstract: Foam cell formation and macrophage polarization are involved in the pathologic development of atherosclerosis, one of the most important human diseases affecting large and medium artery walls. This study was designed to assess the effects of rapamycin and FTY720 (fingolimod) on macrophages and foam cells. Mouse peritoneal macrophages were collected and treated with rapamycin and FTY720 to study autophagy, polarization, and lipid accumulation. Next, foam cells were formed by oxidizing low-density lipoprotein to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
(55 reference statements)
2
17
0
Order By: Relevance
“…It has also been suggested that S1P promotes M1 polarization in macrophages through S1PR3 (50,51) and that FTY720 blocks this polarization and may instead promote M2 polarization (50,52,53). Indeed, we observed that FTY720 treatment induces M2 polarization, which is confined within the fibrotic layer of the granulomas.…”
Section: Discussionsupporting
confidence: 59%
“…It has also been suggested that S1P promotes M1 polarization in macrophages through S1PR3 (50,51) and that FTY720 blocks this polarization and may instead promote M2 polarization (50,52,53). Indeed, we observed that FTY720 treatment induces M2 polarization, which is confined within the fibrotic layer of the granulomas.…”
Section: Discussionsupporting
confidence: 59%
“…Macrophage apoptosis is considered to be a key step in the formation of unstable plaque in atherosclerotic. Macrophage apoptosis is inhibited by FTY-720 and PF-543 through cross-talk of macrophage polarization and autophagy and S1P signal, which helps to prevent the formation of unstable plaque ( Sun et al, 2018 ; Zhu et al, 2020 ). Furthermore, activation of SphK1 is essential in vascular inflammation mediated by inflammatory cytokines such as TNF-α.…”
Section: Role Of Sphingosine Kinase 1 In Inflammatory Immune Related-diseasesmentioning
confidence: 99%
“…Our results showed that DLTs could obviously alleviate macrophage transformation into foam cells (MFI), accumulation of lipid droplets (oil red O staining) and infiltration (CD68) in arterial tissues. The role of autophagy in macrophage lipid metabolism has been highlighted by many researchers (Sun, Fan et al, 2018;Cao, Jia et al, 2019;Zhou, Ren et al, 2019). MD Khurshidul Zahid et al found that enhancing autophagy could drive cholesterol efflux and inhibit macrophagic foam cell formation in RAW264.7 cells (Zahid, Rogowski et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in macrophage lipid metabolism has been highlighted by many researchers ( Sun, Fan et al, 2018 ; Cao, Jia et al, 2019 ; Zhou, Ren et al, 2019 ). MD Khurshidul Zahid et al found that enhancing autophagy could drive cholesterol efflux and inhibit macrophagic foam cell formation in RAW264.7 cells ( Zahid, Rogowski et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%